Anti-CD3 therapy permits regulatory T cells to surmount T cell receptor–specified peripheral niche constraints - Nishio, Junko (The Rockefeller University Press, 2010)
Treatment with anti-CD3 is a promising therapeutic approach for autoimmune diabetes, but its mechanism of action remains unclear. Foxp3(+) regulatory T (T reg) cells may be involved, but the evidence has been conflicting. We investigated this issue in mice derived from the NOD model, which were engineered so that T reg populations were perturbed, or could be manipulated by acute ablation or transfer. The data highlighted the involvement of Foxp3(+) cells in anti-CD3 action. Rather than a generic influence on all T reg cells, the therapeutic effect seemed to involve an ∼50–60-fold expansion of previously constrained T reg cell populations; this expansion occurred not through conversion from Foxp3(−) conventional T (T conv) cells, but from a proliferative expansion. We found that T reg cells are normally constrained by TCR-specific niches in secondary lymphoid organs, and that intraclonal competition restrains their possibility for conversion and expansion in the spleen and lymph nodes, much as niche competition limits their selection in the thymus. The strong perturbations induced by anti-CD3 overcame these niche limitations, in a process dependent on receptors for interleukin-2 (IL-2) and IL-7.